2008
DOI: 10.1590/s0004-28032008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Apendagite epiplóica: aspectos clínicos e radiológicos

Abstract: RESUMO INTRODUÇÃOA apendagite epiplóica (AE) é uma condição clínica incomum, benigna e auto-limitada. Resulta da torção ou trombose venosa espontânea das veias que drenam os apêndices epiplóicos. Manifesta-se por dor abdominal aguda localizada principalmente em quadrante inferior esquerdo (QIE). O diagnóstico se faz por tomografia computadorizada (TC) de abdome. O tratamento é conservador. MÉTODOSPacientes atendidos no Hospital Barra D'Or (HBD), Rio de Janeiro, RJ, entre fevereiro de 2005 e setembro de 2006, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 6 publications
(14 reference statements)
0
33
0
1
Order By: Relevance
“…In our report, we believe that the absence of this finding is enforced by the subacute onset of the pain. A study by Freitas et al (1) found urinalysis alteration in 5% of the patients. No urinalysis changes were observed in the current case.…”
Section: Casementioning
confidence: 94%
See 4 more Smart Citations
“…In our report, we believe that the absence of this finding is enforced by the subacute onset of the pain. A study by Freitas et al (1) found urinalysis alteration in 5% of the patients. No urinalysis changes were observed in the current case.…”
Section: Casementioning
confidence: 94%
“…There were no signs of important abdominal distention, peritonism or fever. The laboratory analysis revealed no signs of infection (leukocytes: 5700/mm (1,2). Other terms such as epiploic appendicitis, appendicitis epiploica, epiploitis, appendagitis, hemorrhagic epiploitis and epiplopericolitis are used interchangeably in the literature (1).…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations